2021
DOI: 10.1021/acsaem.1c00964
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Pt and Ru from Spent Low-Temperature Polymer Electrolyte Membrane Fuel Cell Electrodes and Recycling of Pt by Direct Redeposition of the Dissolved Precursor on Carbon

Abstract: Recovery of platinum group metals (PGMs), namely, Pt and Ru, from a spent membrane electrode assembly (MEA) of a low-temperature polymer electrolyte membrane fuel cell (PEMFC) through environmentally benign and scalable processes is of significant interest and strategic importance for sustainable growth of the renewable energy industries. Here, we report such a scalable and simple process for recovery of Pt and Ru from the spent MEAs from low-temperature PEMFCs, consisting of the Pt and PtRu nanoparticles supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…특히 전기 화학 촉매 지지체는 입자크기, 비표면적 등의 물리적 특성과 촉매 안정성, 활성 등의 전기화학적 특성에 큰 영향을 미친다 [9]. 탄소 지지체는 Pt을 담지하기 위해 가장 널리 사용되는 지지체이다 [10][11][12][13]. 탄소 지지체와 Pt 높은 안정성, (4) 저렴한 비용, (5) 기공 구조 조절 등의 장점을 갖는다 [14][15][16][17].…”
Section: 연료전지(Fuel Cells)은 전기 화학 반응을 통해 화학 에너unclassified
“…특히 전기 화학 촉매 지지체는 입자크기, 비표면적 등의 물리적 특성과 촉매 안정성, 활성 등의 전기화학적 특성에 큰 영향을 미친다 [9]. 탄소 지지체는 Pt을 담지하기 위해 가장 널리 사용되는 지지체이다 [10][11][12][13]. 탄소 지지체와 Pt 높은 안정성, (4) 저렴한 비용, (5) 기공 구조 조절 등의 장점을 갖는다 [14][15][16][17].…”
Section: 연료전지(Fuel Cells)은 전기 화학 반응을 통해 화학 에너unclassified
“…Molecular recognition tactic is also viable due to the specific interaction of Pt IV Cl 6 2− with cucurbituril forming co‐precipitate while leaving Pd II Cl 4 2− and Rh III Cl 6 3− in the solution [78] . Even simpler approaches like p H adjustment (to 13) can be applied for specific Pt and Ru containing solutions that results in Ru‐hydroxide precipitation and therefore addresses the separation problem [79] …”
Section: Platinum Group Metalsmentioning
confidence: 99%
“…[78] Even simpler approaches like pH adjustment (to 13) can be applied for specific Pt and Ru containing solutions that results in Ru-hydroxide precipitation and therefore addresses the separation problem. [79]…”
Section: Selective Precipitationmentioning
confidence: 99%
“…Due to the low binding energy between the catalyst-coated membrane and the CLs, delamination of CLs often occurs throughout repetitive operations. The bonding force supplied by the direct pressing approach of CCM cannot withstand the swelling of the membrane during the operation of the DMFC, resulting in delamination [164]. A study reported that the isotropic membrane swelling (i.e., expansion coefficient difference between the CL and membrane) enhances the variance in swelling ratio with catalyst encompasses a Nafion binder, which would most likely increase electrode layer delamination [165].…”
Section: Pt/ru Delaminationmentioning
confidence: 99%